Development of an advanced nano-satellite (VELOX-I) - mission control system ground station development - Ye, Chuang. (2012)
Since April 2010, NTU has started the development of VELOX-I. It is the First nano-satellite mission of the NTU Undergraduate Satellite Program (USP) and also the First nano-satellite mission in South East Asia. In this Final Year Project (FYP), we aim to develop an operational ground station to ensure a reliable communication link for the command and control of VELOX-I. The scope of this project consists of hardware and software development, link budget calculation and link performance analysis.In this project, the hardware and software architectures have been developed after